P10: LYMPH NODE YIELD IS NOT A RELIABLE PROGNOSTIC MARKER IN ANTERIOR RESECTION AND ABDOMINOPERINEAL RESECTION FOLLOWING NEOADJUVANT THERAPY FOR RECTAL CANCER. (27th April 2021) - Harris, J; Fleming, CA; Ullah, MF; McNamara, E; Murphy, S; Shelly, M; Waldron, D; Condon, E; Coffey, JC; Peirce, CB
Abstract: Introduction: International guidelines recommend a minimum lymph node yield (LNY) of ≥12 for oncological resection in colorectal cancer (CRC). Neoadjuvant chemoradiotherapy (NACRT) decreases LNY, which questions its ability to provide accurate prognostic information. The consensus of this significance remains undetermined. This study aimed to investigate the significance of LNY on recurrence and survival following anterior resection and abdominoperineal resection with or without NACRT for rectal cancer. Method: Prospectively collected data on patients diagnosed with rectal cancer in a tertiary referral centre was interrogated retrospectively. Patients were divided into primary surgery and NACRT groups. Univariable analysis was performed using Fisher's exact test, t-test, and x 2  test, while multivariable analysis utilised a multiple regression model. Disease recurrence and survival was analysed with logrank test for Kaplan-Meier curves. Result: 148 patients were included [56.1% (n=83) receiving NACRT]. The median LNY of the primary surgery group was 14 [interquartile range (IQR) 11-19] and for the NACRT group was 12 (IQR 8-14) ( p  <0.001). Disease recurrence was similar in both primary surgery and NACRT groups. There was a significant decrease in overall mortality in NACRT patients ( p  = 0.03), but there was no significant difference observed in recurrence or mortality amongst LNYs of <8, 8-11, and ≥12. Conclusion: LNY less than 12 was not a negative prognostic indicator following NACRT and surgery for rectal cancer. Take-home message: A lymph node yield of less than 12 is not a negative prognostic indicator in rectal cancer patients who receive neoadjuvant chemotherapy.